Assessing the Risk. (8th August 2016) - Coulton, Nicholas
Abstract : While the English Church shared in celebrating the 800th anniversary of Magna Carta, not least its own part in gaining those rights for everyone, the Church of England was reversing the principle that people are innocent until proved guilty. Such is the pressure of today's concern about child abuse, historic and present. As evidence mounts of the injustices done by false accusations against some high-profile public figures, we are less aware of the toll on other individuals whose turmoil does not hit the headlines. Those teaching and caring are often targeted for claims, and the Church of England has been toughening its procedures.